1999
DOI: 10.1093/oxfordjournals.aje.a010080
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Rotavirus Diarrhea in Egyptian Children and Implications for Disease Control

Abstract: Reliable epidemiologic data are essential for formulating effective policy to control rotavirus disease through immunization. The objective of this study was to describe the epidemiology of rotavirus diarrhea in a population-based cohort of children under 3 years of age residing in Abu Homos, Egypt, in 1995-1996. Rotavirus diarrhea incidence rates (episodes per person-year) were 0.13 for infants aged <6 months, 0.61 for those aged 6-11 months, 0.17 for those aged 12-23 months, and 0.15 for those aged 24-35 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
80
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 20 publications
17
80
2
1
Order By: Relevance
“…The ratio between G1P [8] and G2P [4] is rather unusual since G1P [8] is usually predominant. However, a study conducted in rural Egypt in 1995 and 1996 showed that G2P [4] accounted for 67% of the rotavirus-positive samples (23). It is also noteworthy that G12 was the third most common G type detected in our study.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…The ratio between G1P [8] and G2P [4] is rather unusual since G1P [8] is usually predominant. However, a study conducted in rural Egypt in 1995 and 1996 showed that G2P [4] accounted for 67% of the rotavirus-positive samples (23). It is also noteworthy that G12 was the third most common G type detected in our study.…”
Section: Discussioncontrasting
confidence: 43%
“…In Egypt, diarrheal illnesses are the major causes of morbidity in children under 3 years of age (23). To date, there have been few epidemiological surveys that aimed to determine the circulation of enteric viruses in Egypt and other countries in the Middle East (11,31,36).…”
mentioning
confidence: 99%
“…The results suggest that breast feeding is protective against gastro-enteritis with rotavirus. However, a protective effect of breast feeding has not been consistently found for rotavirus infections, with some population-based studies finding absent or marginal protection [14,16,22,23], whereas a community based study in Egypt found protection [17]. Our study therefore adds to the weight of evidence in favour of the protective effect of breast feeding.…”
Section: Discussionmentioning
confidence: 55%
“…Spread is believed to be faecal oral, through respiratory secretions, person-to-person contact and contaminated environmental surfaces [5]. Breast feeding is thought to confer protection against gastrointestinal pathogens, in particular bacteria [14,15], but there are conflicting results as to rotavirus infection : some authors found no protection [14,16] others have found some protection [17], and others evidence that breast feeding offers protection against severe infection only [18].…”
Section: Introductionmentioning
confidence: 99%
“…In human milk, OPN were highly expressed at both mRNA and protein levels during lactation (Nagatomo et al, 2004), and studies proposed that it might be useful in preventing rotavirus infections during lactating period (Naficy et al, 1999 …”
Section: Introductionmentioning
confidence: 99%